Modern systems analysis and design - Hoffer, Jeffrey A.; George, Joey F; Valacich, Joseph S., 1959- (Upper Saddle River, NJ : Pearson/Prentice Hall, 2005)
Complex, challenging, and stimulating, this book addresses information system analysis and design; it is full of information that shows the organizational process that a team of business and systems professionals use to develop and maintain computer-based information systems. It stresses the importance of responding to and anticipating problems through innovative uses of information technology. The book provides an excellent foundation for systems development, then goes on to making the business case, analysis, design, implementation and maintenance. For future systems analysts, or for those information technology that need a great resource for implementing new ideas and strategies for succes
Chapter 1: The Systems Development Environment -- Chapter 2: The Origins of Software -- Chapter 3: Managing the Information Systems Project -- Chapter 4: Identifying and Selecting Systems Development Projects -- Chapter 5: Initiating and Planning Systems Development Projects -- Chapter 6: Determining System Requirements Chapter 7: Structuring System Process Requirements -- Chapter 8: Structuring System Logic Requirements -- Chapter 9: Structuring System Data Requirements -- Chapter 10: Designing Databases -- Chapter 11: Designing Forms and Reports -- Chapter 12: Designing Interfaces and Dialogues -- Chapter 13: Finalizing Design Specifications -- Chapter 14: Designing Distributed and Internet Systems -- Chapter 15: System Implementation -- Chapter 16: Maintaining Information Systems.
Includes bibliographical references and index
1
Keywords: system design; System analysis